Desenvolvimento de método para remoção de água, sal e sedimento de petróleos do pré-sal empregando radiação micro- ondas - Pinto, Roger Urgel (2019)
In this work was developed a method for removal of water, salt and sediment of pre- salt crude-oil employing microwave radiation in close system, it was used oil in water emulsions with intermediated crude oils (26,7 and 22,4 °API) from pre-salt. It was evaluated the water volume added (0-40 mL) and the irradiation microwave program, the maximum power of radiation (300-800 W), the time at maximum power (10-30 min) and the heating ramp time (10-30 min) were optimized. The method was optimized in order to achieve water content less than 1% (m/m). For the development of the method was used a synthetic emulsion with water content of 20% (m/m) and a median of drop size distribution about 10 μm, then the method was applied to a natural emulsion with 8% (m/m) of water content. Using an aliquot about 10 g of emulsion, 20 mL of water added , a microwave program of 500 W for the power, 30 min of ramp time, 20 min for the time at maximum power and 2 consecutive extraction cycles, it were obtained results for de water content lower than 1%, for both emulsions. Moreover, it was evaluated the salt extraction from crude oil and it was obtained a final Cl concentration, below the required limit (285 mg L-1). Furthermore, it were determined the physicochemical properties (density and °API, dynamic and kinematic viscosity, water content, total acid number, sediment content) and Ba, Ca, Cl, Fe, K, Mg, Na, Ni, S, Sr and V concentration, before and after microwave application. It was observed the reduction of total acid number, sediment content, density and Ba, Ca, K, Mg and Na concentration of the crude oil. Using the optimized method, it were carried out evaluations with pressurized system in presence of inert gas (argon, 5 bar), and also reducing the maximum temperature limit from 270 to 120 °C were evaluated. Finally, the method was applied with conduction and convection heating (crude oil with 8% of water content), and a clear advantaged was shown in the demulsification employing microwave radiation when compared to conduction and convection heating.